PELATIHAN BATIK DENGAN MOTIF JAGAD PACITAN SEBAGAI UPAYA PENGEMBANGAN EKONOMI KREATIF DI DUSUN NGETEP DESA NGROMO KECAMATAN NAWANGAN KABUPATEN PACITAN - Nugroho, Prima; Rahayu Adi Prabowo (Abdi Seni, 2024)
Community service activities with the title "Batik Training with Jagad Pacitan Motifs as an Effort to Develop Creative Economy in Ngetep Hamlet, Ngromo Village, Nawangan District, Pacitan Regency" this activity focuses on improving the skills of the Ngetep Hamlet community through training in the field of fine arts. The program was carried out in order to develop the creative economy in Ngetep Hamlet. This activity is also an effort to present artistic activities which can build the brand image of Ngetep Hamlet. Besides being an effort to improve skills, batik training also aims to grow the love of the community, especially the younger generation, for one of Indonesia's cultural heritages, namely batik. With this training, it is expected that the emergence of artistic activities carried out by the community and can develop into a source of community income in the field of fine arts. The method used in this batik training activity is the lecturing plus method, demonstration, practice, and also combines with the art creation method where participants are invited to be creative in the motifs to be made into batik. This training was carried out with 5 stages of work, namely the introduction of tools and materials, presentation of material about batik, demonstration of the batik making process, practice of motif design creation, and practice of making batik